2017
DOI: 10.4193/rhin17.065
|View full text |Cite
|
Sign up to set email alerts
|

Allergic inflammation is exacerbated by allergen-induced type 2 innate lymphoid cells in a murine model of allergic rhinitis

Abstract: These findings show that ILC2s play a proinflammatory role in the murine AR model, and also highlight ILC2s as a new target in the future AR therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…We also found that the adoptive transfer of NALT-derived nuocytes into the murine AR model exacerbated the allergic inflammation, just like another study from us. 17 Numbers of sneezing, nasal rubbing and infiltrating eosinophils, and expressing levels of IL-5, IL-13, and IL-33 in the NLF were all enhanced significantly when compared to those of the AR group. However, the aforementioned parameters were all reduced after the adoptive transfer of nuocytes transfected by lenti-ORAI1.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We also found that the adoptive transfer of NALT-derived nuocytes into the murine AR model exacerbated the allergic inflammation, just like another study from us. 17 Numbers of sneezing, nasal rubbing and infiltrating eosinophils, and expressing levels of IL-5, IL-13, and IL-33 in the NLF were all enhanced significantly when compared to those of the AR group. However, the aforementioned parameters were all reduced after the adoptive transfer of nuocytes transfected by lenti-ORAI1.…”
Section: Discussionmentioning
confidence: 85%
“…27 A previous study from us demonstrated that allergic inflammation could be exacerbated by OVA-induced nuocytes in a murine model of AR. 17 However, some characteristics of these cells could not be further investigated in that research. In this present study, we aimed to determine Orai1 expression in nuocytes and evaluate the influence of intervention of Orai1 on the response of these cells from AR mice to IL-33.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, Eastman et al found that ILC2s were recruited to the nasal mucosa in patients with aspirin‐exacerbated respiratory disease. Using murine models, two recent researches confirmed the important role of ILC2s in exacerbating type 2 inflammation in AR …”
Section: Introductionmentioning
confidence: 89%
“…Apart from the EUFOREA report, we have a lot of very interesting papers on diverse subjects from allergic rhinitis (19,20) , via risk factors for epistaxis (21) , to surgical papers on inverted papilloma (22) and CSF leak repair (23) .…”
mentioning
confidence: 99%